Mergers and partial tacit collusion - Jens Grüb (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2019)
This paper studies whether mergers may lead to partial tacit collusion, thereby having the potential to induce simultaneous coordinated and non-coordinated effects. We use a Bertrand-Edgeworth model with heterogeneous discount factors to derive conditions for profitable and stable collusion and provide a numerical example. Mergers that change the market structure in a way such that maverick firms are eliminated or colluding firms reach a critical share in total capacity can lead to partial collusion.
urn:nbn:de:bsz:100-opus-16981
Keywords: 330; Partial Collusion; Tacit Collusion; Mergers; Coordinated Effects; Non-coordinated Effects; Umbrella Effects